Análise Mensal [Outubro de 2012] - Pereima, João Basílio; Corrêa, Fernando Motta; Conceição, Ronald; Gomes, Antônio Luiz Costa; Pruss, Caroline; Teixeira, Matheus; Pereira, Gislaine Joyce (Revista Economia & Tecnologia, 2012)
*